"You've got to settle down!": Mothers' perceptions of physical activity in their young children. Issue 1 (December 2015) - Pesch, Megan; Wentz, Erin; Rosenblum, Katherine; Appugliese, Danielle; Miller, Alison; Lumeng, Julie
Abstract Background Mothers are important mediators of children's physical activity (PA) level and risk of obesity, however previous studies of maternal perceptions of child PA have been limited. Furthermore, it is unknown if maternal perceptions of child PA are predicted by family, mother and child characteristics. Therefore objectives of this study were to 1) evaluate maternal perceptions of PA in their children and 2) test associations of family, mother and child characteristics with these perceptions. Methods 278 low-income mothers of children (mean age 70.9 months) participated in an audio-taped semi-structured interview. Transcripts were systematically analyzed using the constant comparative method and themes were generated. A coding scheme to classify the themes appearing in each transcript was developed and reliably applied. Anthropometrics were measured. Demographics and questionnaires (the Confusion, Hubbub and Order Scale, The Parenting Scale, and the Child Behavior Questionnaire (CBQ)) were collected. Logistic regression models were used to test the associations of family, mother and child characteristics with each theme. Results In this sample of low-income United States mothers, two themes emerged: 1) Mothers perceive their children as already very active (87.8 %, n = 244), predicted by the child being younger, the child not being overweight, and higher child CBQ Activity Level; and 2) Mothers view their children's high activity level as problematic (27.0 %, n = 75), predicted by lower Parenting Laxness, the child being male and lower child CBQ Inhibitory Control. Conclusions Low-income United States mothers have unique perceptions of PA in their children; these beliefs are associated with characteristics of the child and mother but not characteristics of the family. Further understanding of contributors to maternal perceptions of child PA may inform future childhood obesity interventions. The influence of these perceptions on physical activity outcomes in low-income children should be pursued in future research.